Effectiveness of Obturator Nerve Mobilization for Knee Joint Pain in Young Females - Ayesha Maqbool, Marium Zafar, Ramesha Tahir, Komal Tariq, Qurat-Ul-Aine, Amina Mehak, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Medial knee pain is reported due to adductor tightness in young females. Nerve supply of adductors of thigh is obturator nerve. Compression of obturator nerve is one of the reasons to generate medial knee pain. Objectives: To evaluate the effect of obturator nerve mobilization for treating medial knee joint pain in young females. Material and Methodology: A quantitative, randomized clinical trial was conducted comprising of sample of 30 patients. Patients were allocated into control group and treatment group randomly by using lottery method. Hot pack and adductor release was given as baseline treatment in both groups. Treatment group received obturator nerve release in addition. Visual analogue scale, Q angle and lower extremity functional scale was used as outcome measures. Results: Data was analyzed by SPSS V.20. Independent sample t-test was used for inter-group analysis, paired sample t-test and repeated measurement ANOVA test was used for intra-group analysis. Significant decrease in medial knee joint pain, Q-angle and lower extremity functional score was reported in treatment group with p value <0.05. Association of BMI with pain and Q angle was found non-significant with p value >0.05. Conclusion: Obturator nerve neurodyanamics showed significant improvement in treating medial knee joint pain in young females. No association was found of BMI with pain and Q angle. Keywords: Young adult, female, Obturator nerve, Nerve compression syndromes, Neurodynamics